O wpływie spuścizny Świętej Teresy z Ávili na piśmiennictwo i kulturę polskiego baroku - Kaczor-Scheitler, Katarzyna (Annales Universitatis Paedagogicae Cracoviensis | Studia Historicolitteraria, 2021)
The subject of this article is to discuss the penetration of influences of Spanish mysticism, in particular, the works of Saint Teresa of Ávila, on the literature and culture of the Polish Baroque. The intercultural influence of Spanish mysticism on Polish artists is reflected in the translations of the writings of Saint Teresa of Ávila. The considerations focus on the influence of the mysticism of Saint Teresa on mystical autobiographies and anonymous poetry of Carmelite nuns from Krakow from the 17th and 18th centuries. The reflection also covers the centres of the veneration of the saint in Poland, in services and prayer books, and her popularisation through art. Mystical influences are also visible in the poetry of the 17th and 18th centuries, including poetry by Kasper Twardowski, Sebastian Grabowiecki, Stanisław Grochowski, Mikołaj Mieleszko, Zbigniew Morsztyn, Maciej Kazimierz Sarbiewski, Elżbieta Drużbacka, and Konstancja Benisławska. The Polish-Spanish ties situate the research issues undertaken in a comparative context, without which the studies on post-Tridentine spirituality would not have produced real achievements.